Disruption of tryptophan metabolism by high-fat diet-triggered maternal immune activation promotes social behavioral deficits in male mice - Penghao Sun; Mengli Wang; Xuejun Chai; Yong-Xin Liu; Luqi Li; Wei Zheng; Shulin Chen; Xiaoyan Zhu; Shanting Zhao (Nature Communications)
Abstract Diet-related maternal obesity has been implicated in neurodevelopmental disorders in progeny. Although the precise mechanisms and effective interventions remain uncertain, our research elucidates some of these complexities. We established that a prenatal high-fat diet triggered maternal immune activation (MIA), marked by elevated serum lipopolysaccharide levels and inflammatory-cytokine overproduction, which dysregulated the maternal tryptophan metabolism promoting the accumulation of neurotoxic kynurenine metabolites in the embryonic brain. Interventions aimed at mitigating MIA or blocking the kynurenine pathway effectively rescued the male mice social performance. Furthermore, excessive kynurenine metabolites initiated oxidative stress response causing neuronal migration deficits in the fetal neocortex, an effect that was mitigated by administering the glutathione synthesis precursor N-Acetylcysteine, underscoring the central role of maternal immune-metabolic homeostasis in male mice behavioral outcomes. Collectively, our study accentuated the profound influence of maternal diet-induced immuno-metabolic dysregulation on fetal brain development and provided the preventive strategies for addressing neurodevelopmental disorders.